Pengaruh Skeptisme Profesional dan Kompetensi Terhadap Kinerja Auditor Internal - Yanti, Kadek Puspa (UNHI Press, 2025)
The role of internal auditors in an organization is very important, auditors are required to produce audit reports that will be used by the company for decision making and determining the direction of policies within the company. The aim of this research is to empirically test and analyze the influence of professional skepticism and competence on the performance of internal auditors. The sampling method used was a probability sampling method with a saturated sampling technique, so that the sample in this study were the internal auditors of the Bali Regional Development Bank, Badung branch, totaling 32 respondents. The data analysis technique uses SEM PLS. The test results show that the performance of the internal auditors of the Badung Branch of the Bali Regional Development Bank is influenced by professional skepticism and auditor competence. The higher the professional skepticism and competence possessed by an auditor, the better his performance will be. Keywords: internal auditor performance, professional skepticism, competence.